KURIKULUM MATA PELAJARAN KEWIRAUSAHAAN BERBASIS TAUHID DI SEKOLAH MENENGAH KEJURUAN (SMK) - Nurhikmah Nurhikmah (Universitas Djuanda, 2015)
The Development of entrepreneurship curriculum in our schools can be reached by many methods, for example: Entrepreneurship that is integrated within learning processes, extracurricular, personal development, local content, and so on. Then realized in Teaching andLearning Activities with the syllabus and lesson plans that integrated with the values of Tawheed. In subjects which includes practicum can be oriented throughout entrepreneurial values. In the tauhidic entrepreneurship curriculum must also contain a variety of essential elements of Qur'an and Hadith, which are entrepreneurial guidance of Islam and containing of history of life of the Prophet Muhammad, Muslim Entrepreneurs Ethics is sourced from exemplary business behavior Prophet, Islamic Entrepreneurship must follow the rules of the Islamic economic system.